Antigenic Structure of Treponema pallidum, Nichols Strain II. Extraction of a Polysaccharide Antigen with “Strain-specific” Serological Activity - Miller, James N. (1969)
An ultracentrifugally homogeneous heat-stable polysaccharide preparation free from serologically reactive rabbit testicular tissue antigen, including cardiolipin, was extracted from the Nichols strain of Treponema pallidum, and found to react by complement-fixation with homologous rabbit sera but not with human syphilitic sera. In addition, the reactive “strain-specific” component was found to be distinct from a second reactive component within the preparation related to an antigen of T. reiteri.